2016
DOI: 10.1210/jc.2015-2706
|View full text |Cite
|
Sign up to set email alerts
|

Relating Phthalate and BPA Exposure to Metabolism in Peripubescence: The Role of Exposure Timing, Sex, and Puberty

Abstract: Considering the long-term health effects related to metabolic syndrome, additional research on exposure and metabolic outcomes across developmental periods and early adulthood is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…Associations of in utero phthalate and BPA exposure with pubertal timing could be mediated through disruption of metabolic homeostasis, as previous studies have demonstrated associations between exposure and altered peripubertal leptin levels (Volberg et al 2013; Watkins et al 2016). Higher levels of leptin are necessary for the onset of puberty, as this signals that energy stores are adequate for reproductive development and maturity (Bordini and Rosenfield 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Associations of in utero phthalate and BPA exposure with pubertal timing could be mediated through disruption of metabolic homeostasis, as previous studies have demonstrated associations between exposure and altered peripubertal leptin levels (Volberg et al 2013; Watkins et al 2016). Higher levels of leptin are necessary for the onset of puberty, as this signals that energy stores are adequate for reproductive development and maturity (Bordini and Rosenfield 2011).…”
Section: Discussionmentioning
confidence: 97%
“…A pediatrician assessed each child to determine Tanner stage for genital (boys), breast (girls), and pubic hair (both) development. For this analysis, we dichotomized pubertal status as prepubertal vs. pubertal: boys were considered pubertal if they received an assessment of Tanner stage >1 for genital or pubic hair development, and girls were considered pubertal if they received an assessment of Tanner stage >1 for breast or pubic hair development (24). …”
Section: Methodsmentioning
confidence: 99%
“…These compounds are of particular interest to the ELEMENT cohort due to their known endocrine-disrupting activities and established association with other metabolic risk factors this population (24, 26). To assess overall in utero exposure, we calculated geometric mean (GM) BPA and phthalate metabolite concentrations for each individual using measurements from each trimester as we have found that this approach provides a more robust measure of exposure for short-lived toxicants, like BPA and phthalates (27, 28).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations